Morphology of the maxilla informs about the type of predation strategy in the evolution of Abelisauridae (Dinosauria: Theropoda) - Enzo E. Seculi Pereyra; Juan Vrdoljak; Martín D. Ezcurra; Javier González-Dionis; Carolina Paschetta; Ariel H. Méndez (Scientific Reports)
Abstract Abelisauridae is a clade of theropods distinguished by short, ornamented skulls and strongly reduced forelimbs. They represented the most abundant predatory dinosaurs in Gondwana during the Cretaceous. Bolstered by biomechanical studies, the morphology of the skull and vertebral column of abelisaurids, have led researchers to hypothesize that Late Cretaceous forms were “specialized hunters.” Here, we use the morphology of the abelisaurid maxilla to test the inclusion of the Lower Cretaceous Spectrovenator within the specialized hunter category. Additionally, we analyze the diversity and disparity of the abelisaurid maxilla in a macroevolutionary context. We quantified the maxillary shape in 17 taxa using 2D geometric morphometrics and analyzed different evolutionary scenarios and trends with phylogenetic comparative methods. The results of all the analyses (phylogenetic ordination methods, Z, and R2 comparison in phylogenetic generalized least squares, model selection, and estimated taxa-removal analysis) suggest that the hunter specialization appeared during the Early Cretaceous, revealing that Cretaceous abelisaurids can be considered specialist hunters. High levels of morphological disparity in the maxilla occurred shortly after the Cenomanian-Turonian faunistic turnover, which involved drastic changes in the South American terrestrial faunal assemblages. Moreover, the high evolutionary rates of the maxillary shape change in Abelisauridae support a shift in ecological pressures or socio-sexual mechanisms, which were the main drivers of the evolution of the clade rostrum. Our study invites to analyze more osteological elements of the abelisaurid skull under a quantitative macroevolutionary framework to test our results more comprehensively.